1999
DOI: 10.1046/j.1365-2133.1999.02879.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma complicating chronic venous leg ulceration: a study of the histopathology, course and survival in 25 patients

Abstract: We have studied 25 cases of squamous cell carcinoma in chronic venous leg ulcers. Twenty-three of the patients were dead and two were alive. The mean age at cancer diagnosis was 78.5 years. The median survival was 1 year. Eleven tumours were well-differentiated, 10 moderately and four poorly. All patients with a poorly differentiated tumour died within a year. Metastases were certain in eight cases. The disease was lethal in 10 cases which included all poorly differentiated tumours. The survival of the study g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
25

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 6 publications
1
52
0
25
Order By: Relevance
“…Similar to other authors (9,14), we think that the treatment of Marjolin's ulcers should not include radiotherapy. This type of treatment does not guarantee effective eradication of the tumour and may be the cause of formation of a chronic wound (9).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Similar to other authors (9,14), we think that the treatment of Marjolin's ulcers should not include radiotherapy. This type of treatment does not guarantee effective eradication of the tumour and may be the cause of formation of a chronic wound (9).…”
Section: Discussionmentioning
confidence: 85%
“…They analysed specimens from the neoplastic lesions and defined the cancer grading once again. They found that while the patients had venous ulceration diagnosed on average at the age of 56.4 and cancer in the ulceration diagnosed on average at the age of 78.5, their survival median was about 1 year and the prognosis was related to the degree of histological malignancy of the neoplasm (9,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although simple bursitis has a well-defined capsule, the lesion in chronic bursitis can appear less well defined due to the inflammation of the surrounding tissues (11,13). Simple prepatellar bursitis, also known as housemaid s knee , is described as an excessive amount of fluid in the bursal space due to inflammation (10,14). and it is easily diagnosed clinically and by MRI with the typical T1 and T2-weighted of fluid within the bursa.…”
Section: Discussionmentioning
confidence: 99%